Information Technology of Estimation and Forecasting Innovative Activity Based on Distributed Data Input; Applied Mechanics and Materials; Vol. 682 : Innovation Technology and Economics in Engineering - Nesteruk D. N. Dmitry Nikolaevich (Management and Economic Aspects Development of Enterprises, 2014)
Title screen